Molecular pathogenesis of cigarette smoking–induced stable COPD. (13th January 2015) - Caramori, Gaetano; Kirkham, Paul; Barczyk, Adam; Di Stefano, Antonino; Adcock, Ian
Abstract : Inflammation is a central feature of stable chronic obstructive pulmonary disease (COPD) and involves both activation of structural cells of the airways and the lungs and the activation and/or recruitment of infiltrating inflammatory cells. This results in enhanced expression of many pro‐inflammatory proteins and reduced expression of some anti‐inflammatory mediators. An altered protein expression is generally associated with concomitant changes in gene expression profiles in a cell‐specific manner. Increased understanding of the role of transcription factors and of the signaling pathways leading to their activation in stable COPD will provide new targets to enable the development of potential anti‐inflammatory drugs. Several new compounds targeting these pathways and/or transcription factors are now in development for the treatment of stable COPD. Furthermore, glucocorticoids drugs already in clinical use act through their own transcription factor, the glucocorticoid receptor, to control the expression of inflammatory and anti‐inflammatory genes.